A new combinatorial identity - Joseph Sinyor; Ted Speevak; Akalu Tefera (International Journal of Mathematics and Mathematical Sciences)
We prove a combinatorial identity which arose from considering the relation rp(x,y,z)=(x+y−z)p−(xp+yp−zp) in connection with Fermat's last theorem.